Integrated optimization of cutting tool and cutting parameters in face milling for minimizing energy footprint and production time. (15th May 2019) - Chen, Xingzheng; Li, Congbo; Tang, Ying; Li, Li; Du, Yanbin; Li, Lingling
Abstract: Cutting tool and cutting parameters are important components in the process planning. Proper selection of cutting tool and cutting parameters can significantly reduce the energy consumption and production time of the machining process. In this paper, an integrated approach of cutting tool and cutting parameter optimization is proposed to minimize the energy footprint and production time of the face milling process. Firstly, the energy footprint characteristics are analyzed by considering multiple cutting tool flexibilities and cutting parameters. Then a multi-objective integrated optimization model for minimizing energy footprint and production time is proposed and solved via a multi-objective Cuckoo Search algorithm. Finally, case studies are conducted to verify the feasibility and validity of the proposed integrated optimization approach. From the results of the case studies, interaction effects between cutting tool and cutting parameters are revealed. Integrated optimization of cutting tool and cutting parameters can achieve more energy footprint savings than either cutting parameter optimization or cutting tool optimization. Moreover, it also can be found that the optimization results for minimum production time does not necessarily satisfy the optimization criterion of minimum energy footprint. The proposed multi-objective integrated optimization approach can strike a balance between minimum energy footprint and minimum production time. Highlights: An integrated multi-objective optimization approach is proposed for face milling. Energy footprint characteristics of face milling are systematically analyzed. Energy footprint and production time vary with cutting tool and parameter schemes. Integrated optimization of cutting tool and parameters saves more energy footprint.